A STUDY ON LISTENING COMPREHENSION PROBLEMS FACED BY SECOND YEAR STUDENTS OF ENGLISH STUDY PROGRAM FKIP - UR - Usti Desliana; Marzuki '; Hadriana ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was aimed at identifying the students’ response to the importance of studying listening comprehension, and finding out problems faced by second year students of English Study Program - FKIP UR in listening comprehension. This study was a descriptive research. The population of this research was the second year students of English study program of FKIP-UR. The sample of this research was selected by using total sampling technique. There were 90 students who participated in this research. The instrument of this research was a set of questionnaire. The questionnaire consisted of two sections. Section one contained questions about students’ self-rated English listening proficiency level (1 item), students’ perceptions related to their high school education (4 items), students’ response to the importance of listenig skill (5 items), and students’ ways of practicing listening skill (5 items). Section two consisted questions about listening comprehension problems grouped into seven categories: listening material (6 items), linguistics aspects (6 items), lack of concentration (5 items), psychological characteristics (5 items), listener (5 items), speaker (5 items), and physical setting (3 items). After all data were collected, the average percentage of each questionnaire item was calculated. The research findings showed that 90.22% of students responded that they realized the importance of English listening skill. It was also found that poor quality of equipments, lack of concentration, un-clear pronounciation, speed rate, unfamiliar word and topic, and psychological problem were the major problems of Listening Comprehension faced by second year students of English study program FKIP University of Riau.Key Words: Study, Listening, Comprehension, Problem